ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN DALAM PEMBAYARAN REKENING LISTRIK - Edy Suhartono (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2015)
In the era of free trade, every company faces stiff competition. The increasing intensity of competition from competitors requires companies to always pay attention to customer needs and strive to meet the expectations of consumers by providing services more satisfactory than those made by competitors. Thus, only a quality company that can compete and dominate the market. Customer satisfaction is influenced by the perception of service quality, product quality, price and the factors that are personal and that is the situation shortly. One of the factors that determine customer satisfaction is the customer perception about the quality of services that focuses on five dimensions of quality, service, namely the physical evidence, responsiveness, and empathy. The purpose of this study was to determine customer satisfaction in the payment of electricity bills in the Village Unit Cooperatives (KUD) Parengan subdistrict. The population in this study is PLJN customers who pay electricity bills through the system Payment Point Online Bank (PPOB) starting in january 2013-december 2013, amounting to 10.378 subscribers. Sample of this research is 99 respondents, with accidental sampling technique.. Methods of data collection using the questionnaire. Teknik analysis used is multiple linear regression.The results shows that quality of service positive effect on customer satisfaction, the reliability factor (X1), being the biggest factor affecting customer satisfaction, and responsiveness (X2), and guarantees (X3) became the lowest factors that affect customer satisfaction. Partially the three variablest significantly affect customer satisfaction (Y).Variable reliability to have the most impact on customer satisfaction, namely amounted to 56.04%, while the variable responsiveness have influence at 12,46% and 3,23% guarantee of customer satisfaction.